2005
DOI: 10.2174/1573394054021718
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Therapy of Melanoma: An Update

Abstract: Objective: To review recent epidemiologic studies of vaccination and melanoma risk as well as critically discuss the different melanoma vaccines under investigation in multicenter phase III melanoma vaccine trials.Data Sources: A retrospective review of the literature.Study Selection: Studies included those on the risk of melanoma and vaccination, historically relevant data, and ongoing or recently published phase III melanoma vaccine trials. The referenced study designs and methodologies varied.Data extractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…9 Recent studies have shown that interferon (IFN) alfa 2b can be given as adjuvant treatment for high risk melanomas and survival rates have improved. 10 Monoclonal antibodies are also considered as second line treatment in non-resectable metastatic melanoma 11 . Malignant Melanoma of Scalp is a aggressive disease and the treatment approach also should be on the same lines.…”
Section: Discussionmentioning
confidence: 99%
“…9 Recent studies have shown that interferon (IFN) alfa 2b can be given as adjuvant treatment for high risk melanomas and survival rates have improved. 10 Monoclonal antibodies are also considered as second line treatment in non-resectable metastatic melanoma 11 . Malignant Melanoma of Scalp is a aggressive disease and the treatment approach also should be on the same lines.…”
Section: Discussionmentioning
confidence: 99%
“…Among potential adjuvant therapies, there remains continued interest in vaccine treatments [34]. The occasional dramatic response of patients with metastatic melanoma to vaccination …”
Section: Status Of Adjuvant Therapy In Melanomamentioning
confidence: 99%
“…These challenges include antigenic heterogeneity, decreased antigen presentation and tumor-induced immunosuppression. While the majority of melanoma vaccines are being evaluated in the metastatic setting, ideally, evaluation should take place of the prevention of recurrence rather than its treatment, since melanoma vaccines should theoretically work best when the tumor burden is lowest [34].…”
Section: Tumor Of Any Thickness With Any Nodes and Any Distant Metmentioning
confidence: 99%
See 2 more Smart Citations